Ответы и объяснения

Лучший Ответ!
  • fou
  • ученый
2013-01-19T16:33:40+04:00

Используем замену переменной.

Восользуемся разложением квадрата:

(x+\frac{1}{x})^{2}=x^{2}+2\frac{x}{x}+\frac{1}{x^{2}}=x^{2}+2+\frac{1}{x^{2}}

Преобразуем исходное:

x^{2}+\frac{1}{x^{2}}-5(x+\frac{1}{x})+6=0\\ (x+\frac{1}{x})^{2}-5(x+\frac{1}{x})+4=0\\ x+\frac{1}{x}=a\\ a^{2}-5a+4=0\\ D=25-16=9\\ a_{1}=1\\ a_{2}=4

Подставляем обратно в замену:

x+\frac{1}{x}=1\\ x^{2}-x+1=0\\ D=1-4<0 \\ \\ x+\frac{1}{x}=4\\ x^{2}-4x+1=0\\ D=16-4=12\\ x=\frac{4\± \ 2\sqrt{3}}{2}=2\± \ \sqrt{3}